Development of Ethanol Extract Combination of Red Shoot Leaves (Syzygium myrtifolium) and Bilimbi Leaves (Averrhoa bilimbi L.) as an Anti-Propionibacterium acnes Agent in Acne Spot Formulation - Micha Mahardika; Isna Lailatusholihah; Miftahul Jannah (Biology, Medicine, & Natural Product Chemistry, 2026)
Propionibacterium acnes is a Gram-positive bacterium and the primary causative agent of acne, which is commonly treated with the antibiotic clindamycin. However, inappropriate use of clindamycin can lead to bacterial resistance. This study explores a natural therapeutic alternative using a combined ethanol extract of red shoot leaves (Syzygium myrtifolium) and bilimbi leaves (Averrhoa bilimbi L.), formulated into an acne spot gel preparation. The objectives of this research were to identify secondary metabolites and to determine the antibacterial effectiveness of the combined extract against P. acnes. Qualitative phytochemical screening, FTIR analysis, and antibacterial activity assays using the disk diffusion method at concentrations of 2.5–10% were conducted to evaluate both the extract and the gel preparation. The results confirmed the presence of flavonoids with O–H (3000–3500 cm-¹), C–O, and C=O functional groups, which are associated with antibacterial activity. The antibacterial activity of the extract showed inhibition zones of 6.5–12 mm, proportionally correlated with concentration. Meanwhile, the acne spot gel containing 17.5% of the combined extract exhibited an inhibition zone of 18.5 mm, greater than that of the commercial product (Wardah acne spot, 15.2 mm), indicating strong inhibitory activity (10–20 mm). Quality evaluation of the gel preparation demonstrated that pH, viscosity, and spreadability complied with the Indonesian National Standard (SNI 16-4399-1996) requirements.